Studi Kualitatif: Praktik Manajemen Sumber Daya Manusia Terhadap Inovasi di Sektor Publik Kabupaten Gresik - Muhammad Maulana Ardiansyah; Khoiril Chilmy; Muhammad Alkirom Wildan (Journal of Management and Creative Business, 2025)
The purpose of this study is to examine the implementation of human resource management (HRM) practices that facilitate innovation in the public sector in a developing country. Qualitative method was engaged whereby a semi-structured interview was conducted to get the responses of two groups of employees which are top management and executive in two types of public organizations which are awarded and non-awarded. The collected data was later analyzed thematically. The results show that there are differences and similarities among the public agencies in terms of their implementation of HRM practices that facilitate innovation. Apparently, the awarded public agencies do follow HRM practices that really facilitate innovation such as local training, provide more types of rewards to their employees and set a higher minimum level of innovation in their performance evaluation. This research confines only 10 public agencies in Gresik. Future studies might want to include a larger sample size to make the findings more extensive. It also would be interesting to know different approaches in HRM implemented in the private organizations as well as to examine their influences on performance and other organizational factors. Good and fair HRM practices such as training, reward and performance appraisal practices that focus on innovation facilitate and produce more innovative employees and organization innovation. Thus, public managers should implement them to a higher extent.